2023
DOI: 10.3390/cryst13030443
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Durability of WAAM 18Ni-250 Maraging Steel Specimens with Surface Breaking Porosity

Abstract: The durability assessment of additively manufactured parts needs to account for both surface-breaking material discontinuities and surface-breaking porosity and how these material discontinuities interact with parts that have been left in the as-built state. Furthermore, to be consistent with the airworthiness standards associated with the certification of metallic parts on military aircraft the durability analysis must be able to predict crack growth, as distinct from using a crack growth analysis in which pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Furthermore, long cracks usually have longer plastic wake that reduces the crack growth rate due to the crack closure effect [31]. Work in [19,[38][39][40][41] has demonstrated that the variability in crack growth rates can be modelled using the modified Hartman-Schijve equation. In this work, Equation ( 6) was used to compute the variability in the crack growth rates in WAAM Ti64, where the material constants D and p were obtained from long crack test data [30].…”
Section: Life Prediction Methodsmentioning
confidence: 99%
“…Furthermore, long cracks usually have longer plastic wake that reduces the crack growth rate due to the crack closure effect [31]. Work in [19,[38][39][40][41] has demonstrated that the variability in crack growth rates can be modelled using the modified Hartman-Schijve equation. In this work, Equation ( 6) was used to compute the variability in the crack growth rates in WAAM Ti64, where the material constants D and p were obtained from long crack test data [30].…”
Section: Life Prediction Methodsmentioning
confidence: 99%
“…Similarly, Appendix X3 (contained) in the fatigue test standard ASTM E647-15el [45] notes that it is not clear if a fatigue threshold exists for small naturally occurring cracks. This finding has significant implications when assessing the durability of metallic airframes since it means that the crack growth equation needed to assess the durability can differ from that associated with the closure free crack growth curve, see [19] for more details. A more detailed discussion on the state of the art can be found in [61,98,99].…”
Section: The Relationship Between Plasticity Induced Crack Closure An...mentioning
confidence: 99%
“…As a result, the DADT assessment of conventionall manufactured, AM and CSAM parts must be based on the appropriate da/dN versus ∆K curve. However, it is now known [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that the variability in the da/dN versus ∆K curves associated with the growth of long cracks in more than one hundred and twenty independent tests performed on a range of additively manufactured (AM) materialscan often be accounted for by expressing the crack growth rate (da/dN) as a function of ∆κ, where ∆κ is the Schwalbe crack driving force [21], and by allowing for the effect of the manufacturing process on just two parameters, namely the cyclic fatigue threshold and the fracture toughness. Here ∆κ is Schwalbe's crack driving force which is defined as:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive manufacturing (AM) has been rapidly developed in the past three decades thanks to the remarkable progress in computer technology and heat source development, which has gained widespread attention due to its high flexibility, high deposition efficiency, and high material utilization [1][2][3][4]. However, limited by the heat source and deposition characteristics, the solidification microstructure of the deposition is dominated by coarse columnar dendrite with significant directional growth due to the temperature gradient [5], leading to significant anisotropy [6], residual stress, and even deformation or crack.…”
Section: Introductionmentioning
confidence: 99%